Lorentz Distributed Noncommutative F(T,TG) Wormhole Solutions - M. Sharif; Kanwal Nazir (Advances in High Energy Physics)
The aim of this paper is to study static spherically symmetric noncommutative F(T,TG) wormhole solutions along with Lorentzian distribution. Here, T and TG are torsion scalar and teleparallel equivalent Gauss-Bonnet term, respectively. We take a particular redshift function and two F(T,TG) models. We analyze the behavior of shape function and also examine null as well as weak energy conditions graphically. It is concluded that there exist realistic wormhole solutions for both models. We also studied the stability of these wormhole solutions through equilibrium condition and found them stable.